Pengaruh Beauty Influencer, Online Customer Review, dan Online Customer Rating terhadap Keputusan Pembeelian Produk Skincare Npure Face Toner - Fadia Chusnul Ma'rifah; Ute Chairuz M. Natusion; Agung Pujianto (Universitas 17 Agustus 1945 Semarang, 2024)
Beauty influencers on social media are key in increasing visibility and sales of beauty products, besides that online customer reviews and online customer ratings also influence purchasing decisions. The purpose of this study is to determine whether beauty influencers, online customer reviews, and online customer ratings on purchasing decisions for Npure Face Toner skincare products. The study design applied is quantitative with an associative approach to analyze the relationship between these variables. The participants in this study consisted of 100 respondents who live in East Surabaya. Sampling using non-probability techniques. The results of this study indicate that partially and simultaneously beauty influencers, online customer reviews, and online customer ratings have a positive and significant influence on purchasing decisions for Npure Face Toner skincare products. This study indicates the importance of digital marketing strategies involving beauty influencers and active management of customer reviews and ratings to increase sales of Npure Face Toner skincare products. Recommendations for the company include increased promotional campaigns involving beauty influencers and responsiveness to customer reviews to increase customer satisfaction.